Antigen induced suppression in peripheral blood and lamina propria mononuclear cells in inflammatory bowel disease. Issue 3 (March 1992) - Dalton, H R; Hoang, P; Jewell, D P
Abstract : Using an autologous system, suppressor cell function to a range of mycobacterial antigens and Kunin antigen of peripheral blood mononuclear cells and lamina propria lymphocytes has been investigated in normal subjects and patients with inflammatory bowel disease. In the peripheral blood there was reduced antigen induced suppression in patients with Crohn's disease in remission to Mycobacterium paratuberculosis, purified protein derivative (PPD), M fortuitum, and Kunin antigens (p less than 0.05). In patients with ulcerative colitis in remission there was reduced antigen induced suppression in the peripheral blood to Kunin antigen (p less than 0.001), M avium (p less than 0.01), M nonchromogenecin, and M fortuitum (p less than 0.05). The phenomenon of antigen induced suppression was largely CD8 dependent, as depleting CD8+ cells reduced the effect and the concentration of soluble CD8 in the culture supernatant was directly related to the suppressor index (r = 0.25, p less than 0.05). These results are likely to be a true reflection of the cell mediated response to antigen as patients with a positive Mantoux skin test have a significantly higher suppressor index to PPD than Mantoux negative subjects (p less than 0.05). These findings may have significance in the aetiopathogenesis of inflammatory bowel disease. However, a similar effect could not be shown in the lamina propria lymphocytes of patients having colectomy for active disease.